Effect of Assessment for Learning (Afol) on Mathemetics Performance Among Senior Secondary School Students in Port Harcourt Metropolis, Nigeria - Opara, Ijeoma Margaret; Uwah, Idongesit Victor (Advances in Social Sciences Research Journal, 2022)
The study investigated Effect of Assessment for Learning (AfoL) on Mathematics Performance among Senior Secondary School Students in Port Harcourt Metropolis. The study adopted the quasi-experimental research design. The population of the study comprised of 3,234 SS2 students drawn across all public secondary schools in Port Harcourt metropolis. A sample of 60 SS2 students across two schools was drawn for the study using purposive sampling technique. Intact class was used without random assignment. The researcher classified the students into the experimental and the treatment groups using the two schools (School A & B) with school A being the experimental group (AfoL) and B (AoL) the control group. These are the assessment for learning group as school A and the control group. The research instrument used for the study was “Mathematics Performance Test” (MPT) which served as pre-test and a reshuffled version serving as the posttest. Table of specification (ToS) was used to determine content and validity of the instrument while KR20 was used to determine a reliability coefficient of 0.91. Mean and standard deviation, t-test and 2-Way ANOVA were used in the analysis. Results showed that there is a significant difference (p=0.000<0.05) in the effect of AfoL on mathematics performance of senior secondary school students in Port Harcourt metropolis as compared between their pretest and posttest scores. There was also a significance difference (p=.021<.05) in the effect of AfoL on mathematics performance of senior secondary school students in Port Harcourt metropolis as compared between the experimental and control groups. On the other hand, there was no significant difference (p=.80>.05) in the effect of AfoL and AoL on mathematics performance of male and female senior secondary school students in Port Harcourt metropolis. Based on this, recommendation among others was that classroom teachers and evaluators should from time to time assess their students (AfoL) instead of waiting till the end of the term (Summative assessment).